The red and the black the Russian Revolution and the Black Atlantic - Featherstone, David, 1974-; Høgsbjerg, Christian (Racism, resistance and social change., 2021)
This edited collection explores the inspiration of the Russian Revolution of 1917 for black radicals across the African diaspora. The volume challenges European-centred understandings of the Russian Revolution and the global left and enables new insights on the relations between Communism and various black radical traditions.